A strategy for fabricating a multifunctional hydrogel with enhanced adhesion and ROS-scavenging capabilities - Pi, Yijie; Yu, Tianwei; Yao, Wen; Xu, JingJing; Peng, YangYang; Cheng, Chiwen; Li, Yanqing; Li, Jiale; Wu, Di; Yu, Yifeng (Frontiers in Materials, 2026)
The cornea is a delicate tissue that is particularly vulnerable to injury, which can lead to blurred vision or even irreversible blindness. It is vital to maintain the cornea’s integrity and transparency throughout the healing process, alongside achieving exceptional biocompatibility. Unfortunately, corneal injuries often result in the excessive production of reactive oxygen species (ROS), which can significantly hinder the healing process. To meet the increasing demand for advanced biomaterials that integrate high transparency, strong adhesion, and effective ROS-scavenging properties for corneal regeneration, this study presents an innovative multifunctional composite hydrogel named GOH-S. This hydrogel is formulated using a careful sequential crosslinking strategy that combines gelatin methacrylate (GelMA), oxidised dextran (ODEX), and thiolated hyaluronic acid (HA-SH). The GOH-S hydrogel features an interconnected porous microstructure and impressive mechanical properties. Its exceptional adhesive strength allows it to securely bond to the wound site, effectively resisting blinking or tear flow and natural eye movements. In testing, GOH-S demonstrated over 85% transparency, minimising visual obstruction for patients while facilitating clinical observation and monitoring. The remarkable potential of the GOH-S hydrogel for corneal repair and regeneration is attributed to its dual functionality: efficient scavenging of harmful ROS and outstanding biocompatibility. This advancement presents a significant opportunity to enhance corneal treatment and improve patient outcomes.